THE POTENTIAL OF CULTURE AS AN INSTRUMENT FOR MANAGING SECURITY CONDUCIVENESS AFTER THE 2024 ELECTIONS IN THE JURISDICTION OF THE SURABAYA POLRESTABES - Himawan, Agung (Jurnal Pemerintahan Dan Keamanan Publik (JP dan KP), 2024)
This study aimed to investigate the existence of cultural potential of Indonesia as an instrument for managing security conduciveness in the jurisdiction of the Surabaya Police. It also aimed to describe the steps taken by the Police and City Government to maximize the potential and realize security stability after the 2024 elections. To achieve this objective, qualitative with a descriptive method was used, and relevant data were obtained from previous literature, documentation observations, and interviews. The results showed that (1) Challenges and inhibiting factors included the erosion of regional culture and language usage, leading to a decline in politeness, brotherhood, love of country, peace, and unity, as well as the rapid flow of information and globalization, fostering aggressive, sadistic, and individualistic behavior, (2) Cultural potential related to the ideas, beliefs, and interpretation of reality in life and love of peace or deliberation could prevent the influence of radical ideas and beliefs to create security conduciveness, (3) The steps taken by the Surabaya Police and City Government included educating the spirit of patriotism and citizenship, visits to religious and community figures, holding sambang and joint patrols, security at religious activities, monitoring the stability of fuel and basic food prices, optimizing forum programs and community partnerships, dealing with conventional crime, improving traffic security, encouraging the younger generation to dive directly into cultural experiences through festivals and promoting information centers. In conclusion, hard work and collaboration between the Surabaya Police, the Indonesian National Armed Forces (TNI), and the City Government could maximize the potential of culture and minimize the inhibiting factors. Therefore, this ancestral legacy was an effective instrument in realizing security stability in Surabaya City after the 2024 Election. Keywords: Cultural Potential; Security Conduciveness, Elections